Betaine decreases hepatic lipid deposition through DNA 5 mC and RNA m6A methylation-mediated regulation of fatty acid metabolic genes expression in laying hens - Yuxin Yang; Xumin Jin; Dengfeng Lu; Yulin Wu; Fanchi Meng; Minyu Zhang; Jiaojiao Wang; Xiaoyan Cui; Tingting Li; Shengchen Wang; Xugang Luo; Yun Hu (Poultry Science, 2025)
As a methyl donor, betaine participates in hepatic lipid metabolism in mammals. Nevertheless, it is unclear whether and how dietary betaine affects hepatic lipid metabolism in laying hens. The current research was conducted to explore the effect of dietary betaine on plasma and hepatic triglycerides (TGs) contents, mRNA and protein expression of fatty acid metabolic genes, and their DNA 5-methylcytosine (5mC) and RNA N6 methyladenosine (m6A) methylation levels in the liver of laying hens. Therefore, a total of 48 laying hens (130-d-old) were randomly assigned to two groups: control and betaine. Hens in control group were fed a corn-soybean meal basal diet without adding betaine, while hens in betaine group were fed the basal diet supplemented with 0.10 % betaine for 35 d. The results showed that dietary betaine decreased (P < 0.05) hepatic TGs content, associated with suppression (P < 0.05) of sterol regulatory element binding transcription factor 1 (SREBP1), fatty acid synthase (FASN) and stearoyl-CoA desaturase (SCD) genes expression, and activation of carnitine palmitoyl transferase 1A (CPT1A) gene expression in the liver. Furthermore, adding betaine to the diet led to higher (P < 0.05) 5mC methylation levels on FASN and SCD genes promoters, and lower (P < 0.05) 5mC methylation levels on CPT1A gene promoter. Besides, the m6A methylation level on the 3′ untranslated region of SREBP1 mRNA was found to be increased (P < 0.05) in betaine-treated chickens. It was concluded that dietary betaine reduces hepatic TGs deposition via DNA 5 mC and RNA m6A methylation-mediated regulation of fatty acid metabolic genes expression in laying hens.